Tingkat Kedisiplinan Guru dalam Menjalankan Tugas (Studi Kasus pada Guru-Guru di SMA Amanah Tahfidz) - Muhammad Ikhwan Hasibuan; Khairuddin Lubis; Hotni Sari Harahap (Departement of Mathematics Education, 2023)
This research was conducted because there was a gap between targets and results in the field of education, researchers took an object of study at a school related to the level of discipline of the teachers who taught at that school. Based on the purpose of this study to measure the level of discipline of teachers at the Amanah Tahfidz Private High School, the researcher took three main points to formulate the problem. First, what is the level of teacher discipline, second, the inhibiting and supporting factors of discipline at the Amanah Tahfidz Private High School, and third, how the impact of teacher discipline in carrying out their duties at the school. The purpose of this research is in this study to analyze the level of discipline of teachers in carrying out tasks in the Quran Tahfidz Amanah School. First, knowing the level of teacher discipline at SMA Amanah Tahfidz. Second, to find out the supporting and inhibiting actors of teacher discipline at SMA Amanah Tahfidz. Third, to find out the impact of teacher discipline in carrying out their duties at Amanah Tahfidz Private High School. While the methodology used in this study is a qualitative research approach. Data obtained from interviews, observation and documentation. Presentation of data is carried out using a descriptive-qualitative approach, by means of analysis using words to retrieve facts, variables and circumstances obtained during the research and explain the words obtained. educational success is achieved, if all related or managers (organizers) of the world of education respect time, are always disciplined in carrying out their work routinely, moreover a teacher is a role model for students, if a teacher cannot provide a good example, then the child -children will not get knowledge perfectly.